Fire and Explosion Risk Analysis and Prevention and Control Technology of Lithium-ion Battery Energy Storage Systems - Suwen Chen; Guanjie Kong; Yalei Zhang; Guoqiang Li (中国工程科学)
In the context of global carbon neutrality and energy structure transformation, the lithium-ion battery energy storage system, as a core infrastructure of a new power system, is experiencing rapid large-scale development. However, fire and explosion risks have emerged as a critical bottleneck, hindering the safe and sustainable development of the energy storage industry. In recent years, frequent safety accidents involving lithium-ion battery energy storage systems, both in China and abroad, have highlighted systemic challenges such as complex mechanisms of thermal runaway, lagging safety prevention and control technologies, and insufficient lifecycle management. This study adopts a "mechanism-assessment-prevention and control" research framework to systematically analyze the causes and evolution mechanisms of fire and explosion accidents regarding lithium-ion battery energy storage systems. It identifies the hierarchical risk characteristics, described as “single cell failure to system-wide failure propagation.” Following a strategy of “battery safety-early warning-hierarchical protection,” the study reviews the current research status of safety prevention and control technologies. Furthermore, it reveals key challenges in the safety prevention and control technologies for lithium-ion battery energy storage systems, including the coexistence of individual technological breakthroughs and systemic defects, imbalance between cost and benefit, emergence of risks in new scenarios, and difficulties in lifecycle safety management. To enhance the safety resilience of lithium-ion battery energy storage systems and support the high-quality development of new energy systems, this study recommends focusing on fundamental research on lithium-ion battery safety, deepening system integration and engineering safety design, strengthening lifecycle safety management, optimizing standards systems and regulatory mechanisms, improving emergency response and insurance systems, and promoting industry chain collaboration and interdisciplinary integration.